PENGARUH MODEL PEMBELAJARAN RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA KELAS IV SD - Putri Astuti, Nabila; Iva Sarifah; Ika Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the Relating, Experiencing, Applying, Cooperating, Transferring (REACT) learning model on students' critical thinking skills in grade IV mathematics learning in elementary school. This study uses an experimental quantitative method, with a pretest-posttest control group design. The population in this study is all grade IV students of public elementary schools in the Pasar Rebo District area for the 2024/2025 school year. The sampling technique used in this study is cluster random sampling, with SDN Cijantung 02 Pagi as the school selected as the research location. From these schools, two classes were designated as samples, namely class IV A (30 students) as the control class and class IV B (30 students) as an experimental class. Data collection was carried out using test instruments in the form of essay questions equipped with rubrics. The data analysis technique was carried out using a t-test assisted by the SPSS 27 program. The results of the analysis showed a significance value of < 0.01, which means it is smaller than 0.05. Based on the results of the hypothesis test, it shows that it is rejected and accepted, it can be concluded that the use of the REACT learning model has a significant influence on students' critical thinking skills in elementary school grade IV mathematics learning. These results can be the basis for the development of the REACT model on a wider range of materials and educational levels.